How low can you go: An investigation of depth sensitivity and resolution using towed marine controlled‐source electromagnetic systems. (23rd March 2023) - King, Roslynn B.; Constable, Steven
Abstract: Understanding the depth of investigation for electromagnetic and electrical methods is important in experimental design and for interpreting inversions. Many studies have defined the depth of investigation for electromagnetic sounding methods, but none have included continuously towed controlled‐source electromagnetic methods. Nodal controlled‐source electromagnetic surveys using ocean‐bottom electromagnetic receivers have generally been found to have a depth of investigation limited to about half the maximum source‐receiver spacing, but experience using continuously towed arrays suggests sensitivity to targets at depths approaching the source‐receiver spacing. We test this on two‐dimensional synthetic data using two methods. A rigorous approach is to re‐invert data as a highly conductive or resistive basement is included at successively shallower depths. When the data misfit becomes unacceptably high we can conclude that the maximum depth of inference has been passed. Rather than rely on overall misfit, we note that it is more realistic to preferentially examine those data most sensitive to largest depths (longest offsets and lowest frequencies). A more practical approach is to determine the depth at which a conductivity contrast can be imaged by inversion, noting that knowledge of a contrast is geologically useful even if the actual conductivities cannot be recovered. Both approaches confirm that the increased data density of towed electromagnetic systems at longest offset increases the depth of investigation to about the maximum offset distance.